(3GdYdGbGJ GdOhdjI GdeYGUQIs (3GdfXQjI hGdJWHjb, GdGSJNOGeGJ GdEYdGejI (B/s - (3GdYhjfj, eMeO Ydjs ((3GdbGgQI (B:s (3ecJHI GdCfLdh GdeUQjI,s, 1982)
(3efGgL GdHMK aj GdYdGbGJ GdOhdjI(B.s
Keywords: (3GdYdGbGJ GdNGQLjIs -- (3efGgL HMKs